Biomass pyrolysis in a micro-fluidized bed reactor: Characterization and kinetics - Yu, J.; Yao, C.; Zeng, X.; Geng, S.; Dong, Li; Wang, Y.; Gao, S.; Xu, G. (Elsevier BV, 2011)
A micro-fluidized bed reactor (MFBR) was developed to enable (1) on-line pulse feeding and rapid heating of particle reactant, (2) effective suppression of the interfacial diffusion via fluidization, (3) minimization of intra-particle diffusion through adoption of fine solid reactants, and (4) on-line monitoring the composition of effluent product gas using, for example, process mass spectrometer. Application of the MFBR to biomass pyrolysis demonstrated that the reactor led the pyrolysis to have higher gas yield and less remaining carbon than the test in TG, and at 1173K the reaction finished in 10s. The time span to release an individual gas component appeared longest for H 2 , shortest for CO 2 and equivalent for CH 4 and CO in between. Reaction kinetics was investigated with respect to the formation of individual gas component and pyrolysis gas mixture. The resulting activation energy and preexponential factor with respect to gas mixture were 11.77kJ/mol and 1.45s -1 , respectively. These values were obviously lower than those measured with TG and fixed bed reactors, reflecting the quick reaction nature enabled by the MFBR. A consequent comparison revealed further the factors that affect the values of the kinetic parameters. © 2011 Elsevier B.V.